Indoor environment and energy efficiency in schools. Part 1, - Alfano, Francesca R. d'Ambrosio; Bellia, Laura, 1960- (REHVA guidebook, 2010)
School buildings represent a significant part of the building stock and also a noteworthy part of the total energy use. Indoor and Energy Efficiency in Schools Guidebook describes the optimal design and operation of schools with respect to low energy cost and performance of the students. It focuses particularly on energy efficient systems for a healthy indoor environment.